THE NEW US ADMINISTRATION: PERSPECTIVES FOR RUSSIA. THE PAPERS OF THE INTERNATIONAL “ROUND-TABLE” CONFERENCE - Dutkewicz, P.; Pochta, Yu.M.; Kochetkov, A.P.; Blochin, K.V.; Frolova, O.A.; Hovhannisyan, A. (RUDN Journal of Political Science, 2017)
March 3, 2017 the Department of comparative politics, faculty of Humanities and social sciences held an international “Round-table” conference “The new US administration: perspectives for Russia”, which discussed issues related to the functioning of the new U.S. Administration after the election of Donald Trump.